Promotion Strategy for the Film Gatotkaca by Hanung Bramantyo Using the AISAS Approach - Wirasari, Ira; Wicaksono Nugroho, Kevin Wisnu (LP2M ISBI Bandung, 2025)
Superhero-themed films are currently prevalent in the international film market. Satria Dewa Studio released Gatotkaca as the opening film for its franchise universe. This type of research is descriptive qualitative, with observations to analyze the promotional strategy for the Gatotkaca film using the attention, interest, search, action, and share (AISAS) marketing model. The results of this research are that promotional strategies carried out using the AISAS approach model can increase public awareness of Gatotkaca figures. The film Gatotkaca was promoted in conjunction with the branding process to complement each other and increase ticket sales for the film Gatotkaca. The branding process was carried out using the identity of the Gatotkaca character, namely the star symbol and gold color applied to the film title logo and also the costume design of the Gatotkaca character; it could increase public awareness, ticket sales and Gatotkaca film merchandise.